Dari sampah jadi wah! Jelantah disulap jadi lilin aromaterapi unik dan berdaya jual - Ramadhani, Filiza Alyedia (Maliki Interdisciplinary Journal, 2025)
Household waste, particularly used cooking oil (commonly known as "jelantah"), poses a significant environmental challenge. This project aims to transform used cooking oil into a valuable product—aromatherapy candles—as a contribution to waste reduction and environmental awareness. The production process was carried out by university students in collaboration with the community of Merjosari Village, involving several stages: collection, filtration, material mixing, molding, and public dissemination. The project demonstrated that used cooking oil can be recycled into economically valuable and educational products. The resulting aromatherapy candles not only function as air fresheners but also serve as an inspiration for the creative and sustainable reuse of household waste. Project analysis indicates strong sustainability potential through the application of circular economy principles and increased public awareness regarding domestic waste management.